Understanding and encouraging giftedness. Theoretical and applicative aspects - D'Alessio, Chiara (Formazione & insegnamento, 2018)
This work intends to offer a psycho-pedagogical look to the term giftedness including general intelligence, specific talent, creativity, motivation, dwelling on dimensions that characterize the subjects that demonstrate such skills in school activities or in extracurricular ones, trying to identify potential and problems related to the presence of these skills. The combination of these factors, unique in each subject, leads gifted to own different intellectual strengths and personality traits, even if they are not always easy to manage. Independence, strong energy, nonconformism and anticonventionalism, stubbornness, resistance, lack of cooperation, indifference to the rules, cynicism, neglect, traits that must be channelled into a mature creative behavior, dictated by abilities residing in a personality that has dimensions conducive to creativity and an inner thrust to strive in central areas for the existence. The desire to complete a state of unsatisfactory things is the catalyst of creative behavior and to allow a creative potential to manifest consistently and meaningfully, it is a central matter the early identification and the stimulus of interests, motivation and habit to consider their work also from the point of view of social utility, just from the school experience.